INFLUENCE OF TEMPERATURE AND A LONG TIME DRAINING TO QUALITY CANDY OF DRY JAHE (Zingiber officinale Rosc.) AND INGGREDIENT OF ANTIOXIDANT - Shanti Fitriani; Akhyar Ali; Widiastuti ' (Jurnal Sagu, 2013)
The effects of different drying temperatures (40 C, 50 C and 60 C) and drying times (3, 4, 5 and 6 hours) onthe production of dried sweetened ginger and content of its antioxidant had been studied. The purpose of thisresearch was to find out the drying time and temperature with the best quality and minimal losses ofantioxidant content. It was also to know the panelists acceptance of this product. A completely RandomizedDesign was used in this research which take places at Agricultural Product and Food Chemistry Laboratory,Riau University and Organic Chemistry, Bandung Institute of Technology. The results show that the differentdrying temperatures and times significantly affected the water and sucrose content, but did not significantlyinfluence the ash contents. The gingerol content was almost not detected in the final product. Combinationdrying temperature 50 o C and drying time 3 hours exhibited the best panelists acceptance, and combinationof 50 o C with 4 hours drying showed the best quality of dried sweetened ginger that met the SNI 01-04443-1998 (water content 37,499%, ash content 2,756% and sucrose 36,133%).Key words: Zingiber officinale, temperature, long time draining, quality, antioxidant